Mead's Symbolic Interactionism Analysis of Nadhifa Allya Tsana's Online Identity on Social Media Instagram @ntsana: Analisis Symbolic Interactionism Mead terhadap Identitas Daring Nadhifa Allya Tsana Di Media Sosial Instagram @ntsana - Salma, Aprilina; Amalia, Shira Putri (Universitas Muhammadiyah Sidoarjo, 2025)
In the modern digital era, technological advancements have significantly transformed how individuals communicate, construct identities, and present themselves, particularly on social media platforms. Social media, once a mere communication tool, has evolved into a sophisticated stage where people actively negotiate and perform their self-representations. Instagram, among the most widely used social media sites, is essential to shaping personal branding and online identities. This study examines the digital identity construction of Nadhifa Allya Tsana, widely known as Rintik Sedu, through the lens of George Herbert Mead's Symbolic Interactionism theory. Tsana, a successful writer, content creator, podcaster, and entrepreneur, utilizes Instagram to build and communicate her identity, engaging in a dynamic process of symbolic interaction with her followers. This research aims to explore how Tsana constructs her online identity, interacts symbolically with her audience, and utilizes various symbols to communicate and reinforce her self-image on social media. By analyzing her Instagram posts, captions, and interactions with followers, This study emphasizes how verbal and visual signals contribute to the formation of a personal narrative and fostering emotional connections with her fanbase. Additionally, the research addresses the challenges and opportunities of managing a digital identity, including issues like plagiarism and the preservation of authenticity. Ultimately, this study underscores the importance of symbolic interaction in the digital age, where individuals not only shape their identities but also interact with society through shared symbols in an interconnected online space.